Competition on the main domestic trunk routes (Civil Aviation Authority LondonGB, 1987)
Examines the changes that have taken place in the four main domestic trunk routes to determine the effects on both the airlines concerned and the passengers travelling on these routes. Attempts to identify the role which increased airline competition may have played. Also examines changes occuring on other routes, domestic and short-haul European, as well as the magnitute of effects resulting from macro-economic factors.
DC